Surface profile measurement using a laser displacement sensor - Talukdar, Amitava (2008)
A three dimensional surface profiling system was developed by integrating a Confocal laser displacement sensor with a X-Y scanning stage. The system allowed to scan a sample point by point over a selected area. For each point on the sample X, Y and Z values were collected. The collected data were used to create a three dimensional topographic map of the surface of the sample. The samples were chosen from semiconductor industry having high aspect ratio structures, abrupt changes in color, engraved marks on porous black surface etc. The Confocal displacement sensor operating in reflection mode is capable of discriminating depth of samples with such properties as the reflected signal it measures to discriminate depth is the relative peak intensity of the reflected light. This measuring principle allows it to adapt to a change in signal caused by artifacts such as surface properties, changes in color, surface roughness etc other than change in depth. Finally the specification of the system was determined with respect to resolution, scanning time and scanning speed.